Development and Validation of a Clinical Assessment Tool for Platysmal Banding in Cervicomental Aesthetics of the Female Neck. (27th July 2015) - Gupta, Subhas; Biskup, Nataliya; Mattison, Gennaya; Leis, Amber
Abstract : Background: In facial aesthetics, grading systems are useful tools for planning aesthetic procedures. One key component of rejuvenation—the anterior neck—has been relatively overlooked. In the 1980s, criteria were established for the appearance of a youthful neck. Considering the significant contribution of the anterior neck to the aesthetics of the lower face, updated and more extensive clinical evaluation tools are critical to successful execution and measurement of rejuvenation. A validated assessment scale has yet to be created for platysmal banding, one component of the anterior neck that significantly contributes to the aesthetics. Objectives: The purpose of this study was to establish a validated platysmal banding scale for clinical application. Methods: Three-dimensional standardized photographs from over 100 volunteer patients of various ages and ethnicities were analyzed to develop a five-point scale for platysmal banding. The scale was validated by a group of academic and nonacademic attending plastic surgeons as well as senior level plastic surgery residents then analyzed through a two stage process to ensure both interrater and intrarater validity. Results: We measured the Intraclass Correlation Coefficients (ICC) for the interrater reliability. ICCs ranged from moderate to excellent agreement. Cronbach's alpha, which represents intrarater reliability, was also calculated for the same sample with all results being good to excellent. Conclusions: This study established a validated scale to assess the degree of platysmal banding in the female neck. This grading system has potential application in the preprocedure planning for patients considering face and neck rejuvenation to address platysmal banding.